Peptic Ulcer - Martin, Lay (1942)
I have tried to give a brief account on some of the aspects which in my opinion, are of interest and importance in order to understand and to treat a patient suffering with peptic ulcer. That means a consideration of both: the patient and the ulcer as in this association much of the progress of the disease depends of the patiens psycological condition. In a very short time 1 hope a day will come in which peptic ulcer shall be considered only as a medical disease. When it happens the patient who needs surgery will not be a medical treatment's failure but someone who has not received an attention of kindness and understanding.